Struggles and Oppression in Maya Angelou Poetry Based On Marxism Perspective - Revinda Simarmata (Faculty of Education and Teachers Training, 2019)
This objectives of this research is to know the influences of struggles and oppression in Maya Angelou poetry based on marxism perspective, to know how the poet overcome of struggle and oppression in class community through Marxism perspective and Also to know the moral messages contained in Maya Angelou poetry through Marxism perspective. The data of this research collected from various sources through browsing on internet and listening to the audio of the poetry to support the data analysis. In this research, the writer using descriptive qualitative method as a method of analysis. Theory that the writer used to analyses struggle are from Arindani (2016), and for analyses oppression are from omidvar (2016). The result of this research are: 1). The influences of struggles and oppression make poet become strenght, 2). The poets comes out from life struggles and oppression through leaving behind an oppression and 3). There are many moral messages contained in Maya Angelou Poetry.